A Survey on Cognitive Network Spectrum Sensing and Routing Techniques - Dr. Snjeev Kumar Gupta (Dean), , Phd Scholar Rohit Kumar, Dr. Laxmi Singh (Design Engineering, 2021)
Data dependency increases communication between users, companies, organization, nations, etc. This high demand of transferring data directly depends on spectrum utilization. As primary license companies purchase it in bulk, so cost gets reduced and utilization is less. This issue was resolved by cognitive radio networks by sensing channel status (Free / Occupied) and transfer data. One more problem of cognitive radio network is routing. Paper has brief requirement of dynamic spectrum sensing and its cycle. Some of routing issues were also list by the paper to improve excising work of this field. Techniques of channel sensing were also detailed in the paper. Research works done by other researcher were explained for channel sensing and routing to optimize spectrum.